The Beneficial Effects of Actinomycetales Immune Modulators in the Pancreas of Diabetic Rats - Monireh Khordadmehr; Solin Ghaderi; Mehran Mesgari-Abbasi; Farinaz Jigari-Asl; Katayoon Nofouzi; Hossein Tayefi-Nasrabadi; Graham McIntyre (Tabriz University of Medical Sciences, 2021)
Purpose: Type 1 diabetes mellitus (T1DM) has dramatically increased in recent years, especially in young people, and limits the life quality of the patients involved. Thus, many researchers are performing extensive studies to find alternative treatments for DM. Methods: Here, we evaluated the improvement effects of the heat-killed Actinomycetales species, including Gordonia bronchialis, and Tsukamurella inchonensis in streptozotocin (STZ)- diabetic rats by biochemical, immunological, and histopathological examinations. Results: The present findings exhibited a dramatic and progressive alteration in the serum levels of interleukin-6 (IL-6), IL-10 and tumor necrosis factor-α (TNF-α) in the diabetic group, which were related to the blood glucose and insulin levels, oxidative stress defense (evaluated by TAC and MDA activities), and the pancreas biochemical indicators (such as amylase and lipase). More importantly, the present results were consistent with the histopathological findings, which included cellular degeneration, vascular congestion, hemorrhage, focal necrosis associated with mononuclear cell infiltration. Interestingly, all of the diabetic changes in the blood serum and tissues improved remarkably in the treated groups by Actinomycetales species. Conclusion: Surprisingly, most of the current diabetic complications effectively attenuated after oral administration of both Actinomycetales species, particularly with a high dose of T. inchonensis. Thus, it is concluded that the heat-killed Actinomycetales species can prevent and improve the progression of T1DM and its various complications profoundly.